A multicenter phase IV study to investigate the immunogenicity of recombinant human follicle-stimulating hormone and its impact on clinical outcomes in females undergoing controlled ovarian stimulation - Abha Majumdar; Le Hoang; Ly T Loc; Padma Srivastava; Chitra Ramamurthy; Ratnabali Chakravorty; Yogeshwar S Nandanwar; M D Rashmi; Rahul V Mayekar; Jayashree Sridhar; Ganesh H Divekar; James John (Wolters Kluwer Medknow Publications, 2019)
Context: Therapeutic proteins can cause immune responses, which may have clinical implications. Aims: The aim of the study was to assess the immunogenicity of recombinant human follicle-stimulating hormone (r-hFSH), when used for controlled ovarian stimulation (COS). Settings and Design: Prospective, multicenter study conducted at reproductive medicine clinics in India and Vietnam. Materials and Methods: A total of 285 women, aged 20-40 years, undergoing 354 COS cycles for either intrauterine insemination (IUI) orin vitro fertilization (IVF) were studied. The primary outcome measure was the incidence of development of anti-drug antibodies (ADA) and their neutralization potential. Other outcome measures were follicle development, dose and duration of r-hFSH, positive serum pregnancy test, clinical pregnancy, cycle cancellation, and adverse events (AEs). Statistical Analysis Used: A sample size of 250 was planned. Descriptive statistics are presented. Results: Four patients tested positive for ADA after r-hFSH administration at different time points; all of them tested negative, subsequently. None were found to have neutralization potential. The mean dose and duration of r-hFSH were 816 IU and 8.1 days in IUI and 2183 IU and 9.5 days in IVF, respectively. The serum and clinical pregnancy rates were 12.4% and 11.6% in IUI and 32.7% and 29.9% in IVF cycles, respectively. Seven AEs were reported, including two cases of ovarian hyperstimulation syndrome; two AEs were judged to be serious. Conclusions: The tested r-hFSH has very low immunogenic potential and did not lead to the development of neutralizing antibodies. The overall efficacy and safety of the drug were in-line with existing literature data, and no specific clinical impact of immunogenicity could be identified.